1999
DOI: 10.1177/105381519902200407
|View full text |Cite
|
Sign up to set email alerts
|

Effects of First Aid Training Using Small Group Instruction With Young Children With Disabilities

Abstract: Nine children, ages 41 to 69 months, participated in this study examining the effects of a first aid training procedure on the acquisition, maintenance and generalization of seeking adult assistance in response to simulated injuries. A multiple baseline probe design across children was used to measure number of response steps completed correctly, duration of responding, and obtaining adult assistance. First aid training was conducted in triads consisting of one target learner and two non-target group learners.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
2
8
0
2
Order By: Relevance
“…The participants have acquired the first aid skills by performing all steps decided by analyzing the target skills. This research has findings that support relevant studies aimed at teaching first aid skills to students with different disabilities such as developmental and intellectual disability (Christensen et al, 1993;Ergenekon, 2012;Gast, Winterling, & Wolery, 1992;Marchand-Martella & Martella, 1990;Kearney et al, 2018;Spooner, Stem, & Test, 1989;Timko & Sainato, 1999). In a similar study, Gast et al (1992) examined the effectiveness of a training package in teaching first aid skills through constant time delay procedure to students with intellectual disability with a small group format.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The participants have acquired the first aid skills by performing all steps decided by analyzing the target skills. This research has findings that support relevant studies aimed at teaching first aid skills to students with different disabilities such as developmental and intellectual disability (Christensen et al, 1993;Ergenekon, 2012;Gast, Winterling, & Wolery, 1992;Marchand-Martella & Martella, 1990;Kearney et al, 2018;Spooner, Stem, & Test, 1989;Timko & Sainato, 1999). In a similar study, Gast et al (1992) examined the effectiveness of a training package in teaching first aid skills through constant time delay procedure to students with intellectual disability with a small group format.…”
Section: Discussionsupporting
confidence: 58%
“…Giving correct reactions in situations where first aid is needed is one of the vital social life skills for individuals (Marchand-Martella & Martella 1990;Spooner, Stem, & Test, 1989). In addition, the first aid skills enable the ones with intellectual and other disabilities to live more independently (Timko & Sainato, 1999). Therefore, they must systematically be taught to individuals in both groups.…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen studies reported the effect on first-aid skills6 12 16 21 22 27 29–35, and eleven demonstrated significantly greater first-aid skills in the intervention group than the control group during the post-training periods 6 12 16 21 22 27 29–33. Five of the seven studies that recruited only children or young peopled demonstrated significantly greater first-aid skills6 16 21 22 29 in the intervention group than the control group during the post-training periods, and the remaining two studies did not report the significance of the improvements in first-aid skills seen 34 35. One study evaluated the effect of using handheld computer assistance and measured the outcomes during the computer-assisted training;33 otherwise, post-training periods ranged from immediately post-training to 13 months, suggesting some evidence of a longer-term effect.…”
Section: Resultsmentioning
confidence: 97%
“…Güvenlik becerileri, gelişimsel yetersizliği olan bireylerin yaşamlarını güven içinde sürdürebilmeleri, toplumsal etkinliklere tam katılım sağlayabilmeleri, bir işte çalışabilmeleri ve toplumda bağımsız bireyler olarak yaşamlarını sürdürebilmeleri için gerekli olan becerilerdir (Taber, Alberto, Seltzer ve Hughes, 2003;Timko ve Sainato, 1999). Bu beceriler bireyin evde, okulda, işyerinde ve/veya toplumsal ortamlarda güvenliğini tehdit eden acil, beklenmedik ve tehlikeli durumları fark etmesi, bu durumlara karşı uygun sürede uygun davranışları sergilemesi, kendini koruması ve kişisel güvenliğini sağlaması gibi (Bambara, Browder ve Koger, 2006;Bambara, Koger ve Bartholomew, 2014;Dixon ve ark., 2010) içinde hem psiko-motor hem de bilişsel farklı pek çok davranışı barındıran geniş bir beceri yelpazesinden oluşur.…”
Section: Güvenlik Becerileri Ve Sınıflamasıunclassified
“…Bunun yanı sıra, BEP'lere güvenlik becerilerinin öğretimiyle ilgili amaçlar konması ve bu becerilerin gelişimsel yetersizliği olan bireylere erken yaşta kazandırılması, bireylerin bulundukları çevrede tehlikeleri fark etmelerini ve tehlikelerden korunma konusunda daha dikkatli olmalarını sağlayacaktır. Ayrıca, bireylerin bu becerilerde kazandığı yeterlik daha ciddi kazaları ve yaralanmaları da önlemeye hizmet edecektir (Timko ve Sainato, 1999).…”
Section: Agran Ve Krumpunclassified